Equine endometrial cytology: Collection techniques and interpretation. (3rd February 2015) - Ferris, R. A.; Bohn, A.; McCue, P. M.
Summary Endometritis is an important cause of reproductive pathology in the horse. Endometrial cytology preparations from unguarded swabs, guarded swabs or brushes, cap of a guarded swab, low volume lavage or even an endometrial biopsy sample can be utilised to rapidly evaluate uterine health. These cells can easily be stained with a modified Wright's stain and evaluated for the presence or absence of inflammatory cells and pathogens. Commonly visualised cell types are easily identified with a traditional light microscope at 400× or 1000× magnification. This technique provides an easy and rapid way to diagnose endometritis in the horse.